A New Synthesis of Polyfunctionalized 2-Alkyl-1,4-diketones - Palmieri, Alessandro; Gabrielli, Serena; Sampaolesi, Susanna; Ballini, Roberto (Synlett, 2015)
The reactivity of silyl enol ethers with β-nitroenones was successfully exploited for synthesizing functionalized polycarbonyl frameworks, in very short reaction times and in good yields.
Keywords: Michael addition; enones; nitro compounds; silyl enol ethers; 1,4-dicarbonyl derivatives